Formal methods for industrial critical systems : 24th international conference, FMICS 2019, Amsterdam, the Netherlands, August 30-31, 2019 : proceedings /: 24th international conference, FMICS 2019, Amsterdam, the Netherlands, August 30-31, 2019 : proceedings. ([2019]) - Unknown
No abstract available